2017
DOI: 10.1186/s13018-017-0539-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Singh Index and Osteoporosis Self-Assessment Tool for Asians as risk assessment tools of hip fracture in patients with type 2 diabetes mellitus

Abstract: BackgroundType 2 diabetes mellitus (T2DM), an epidemic disease around world, has recently been identified as a risk factor for osteoporosis-associated fracture. However, there is no consensus on the best method of assessing fracture risk in patients with T2DM. The aim of this study was to evaluate the usefulness of the Osteoporosis Self-Assessment Tool for Asians (OSTA) and the Singh Index (SI) in hip fracture risk assessment in patients with T2DM.MethodsWe enrolled 261 postmenopausal women with T2DM: 87 had h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…In comparison with other fracture prediction tools, the performance of OST was weaker than DXA [ 58 ] and FRAX [ 58 ] in Chinese men and the Singh index in patients with type 2 diabetes mellitus [ 60 ]. However, a study showed that USPSTF (FRAX) (sensitivity = 25.8%; specificity = 83.3%; AUC = 0.56) was not better than OST in fracture prediction (sensitivity = 39.8%; specificity = 60.7%; AUC = 0.52) among non-Asian postmenopausal women [ 54 ].…”
Section: Ost For Fracture Predictionmentioning
confidence: 99%
“…In comparison with other fracture prediction tools, the performance of OST was weaker than DXA [ 58 ] and FRAX [ 58 ] in Chinese men and the Singh index in patients with type 2 diabetes mellitus [ 60 ]. However, a study showed that USPSTF (FRAX) (sensitivity = 25.8%; specificity = 83.3%; AUC = 0.56) was not better than OST in fracture prediction (sensitivity = 39.8%; specificity = 60.7%; AUC = 0.52) among non-Asian postmenopausal women [ 54 ].…”
Section: Ost For Fracture Predictionmentioning
confidence: 99%
“…This means that a high percentage of subjects categorized as moderate or high risk for osteoporosis by the OSTA actually have normal bone health status based on the bone densitometry (false-positive). Second, some studies showed that OSTA alone did not satisfactorily predict fracture risks in subjects with pre-existing medical conditions [ 53 ]. Considering the incidences of comorbidities are higher in high-risk and medium-risk patients than that in the low-risk patients, bias would possibly result among the patients with different risk to osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…3 Radiological grading of osteoporosis was done using Singh's Index. 4,5 The clinical and functional outcome was calculated using the Kyle's criteria. 6,7 All surgeries were performed under spinal anesthesia, internal fixation with dynamic hip screw and 135 o angled blade plate.…”
Section: Methodsmentioning
confidence: 99%